2021
DOI: 10.1093/nar/gkab460
|View full text |Cite
|
Sign up to set email alerts
|

Human MettL3-MettL14 RNA adenine methyltransferase complex is active on double-stranded DNA containing lesions

Abstract: MettL3-MettL14 methyltransferase complex has been studied widely for its role in RNA adenine methylation. This complex is also recruited to UV- and X-ray exposed DNA damaged sites, and its methyltransfer activity is required for subsequent DNA repair, though in theory this could result from RNA methylation of short transcripts made at the site of damage. We report here that MettL3-MettL14 is active in vitro on double-stranded DNA containing a cyclopyrimidine dimer – a major lesion of UV radiation-induced produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 96 publications
7
41
0
Order By: Relevance
“…7). This result was consistent with other studies showing that YTHDC1 is recruited to sites of DNA damage, bound m 6 A RNA, and increased the activity of DSB repair (Yu et al, 2021a;Zhang et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…7). This result was consistent with other studies showing that YTHDC1 is recruited to sites of DNA damage, bound m 6 A RNA, and increased the activity of DSB repair (Yu et al, 2021a;Zhang et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, knockdown of YTHDC1 impeded METTL3-enhanced RAD51 expression and inhibited recruitment of RAD51 to damaged sites. Our data combined with the studies of Zhang et al and Yu et al demonstrate that YTHDC1 plays an important role in DNA repair (Yu et al, 2021a;Zhang et al, 2020). Our results further suggest the involvement of YTHDC1 in the regulation of EGF mRNA stability.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Moreover, N6-methyladenine (N6mA) reduced misincorporation of 8-oxo-guanine (8-oxoG) opposite to N6mA by repair DNA polymerases. When 8-oxoG is incorporated into the opposite site to N6mA, this process inhibits N6mA excision from the template [48]. From this observation, it is evident that METTL3/METTL14 methyltransferases, together with m 6 A RNAs, are required for DNA damage repair mechanisms that are initiated by UV radiation [23,24].…”
Section: Discussionmentioning
confidence: 97%
“…Yu et al (2021) [48] showed that the function of the METTL3-METTL14 complex, similarly to m 6 A RNA nuclear reader YTHDC1, contributes to the repair of DNA lesions containing cyclobutene pyrimidine dimers, which are well-characterized elements that appear after UVirradiation. Moreover, N6-methyladenine (N6mA) reduced misincorporation of 8-oxo-guanine (8-oxoG) opposite to N6mA by repair DNA polymerases.…”
Section: Discussionmentioning
confidence: 99%